Congress volume Helsinki 2010 - Nissinen, Martti. (Vetus Testamentum, Supplements, 2012)
This volume brings together the main contributions to the 20th congress of the International Organization for the Study of the Old Testament (IOSOT) held in Helsinki, Finland in August, 2010. The 24 articles discuss the following five topics: Archaeology and texts, with an emphasis on the Persian Period; Qumran, the Septuagint and the Textual History of the Hebrew Bible; Deuteronomistic texts, with a special focus on the question "What is 'Deuteronomistic?'"; Wisdom and Apocalypticism; and methodological and interdisciplinary issues such as Bible and art and intertextuality. The volume gives readers an up-to-date view of the most recent developments in the research of these topics and the study of the Hebrew Bible in general.